The effects of health aid on child health promotion in developing countries: cross-country evidence - Osman Ouattara (Applied Economics, 2013)
Although epidemiological knowledge in relation to child health has improved in the last few decades, around 3 million children die each year in developing countries from preventable diseases. The international development community views increased immunization coverage for children as an important step in eliminating or reducing these deaths. Many developing countries have very limited resources to tackle major health problems and have to rely on external finance. This article examines the impact of foreign aid devoted to the health sector on child health promotion in developing countries. Two proxies for child health promotion are used: (a) immunization against measles and (b) immunization against Diphtheria–Pertussis–Tetanus (DPT). A range of model specifications and panel data econometric techniques are applied to data covering the period 1990 to 2005. This article finds a positive and statistically significant link between health aid and the measures of child health promotion.